Fundamentals of Engineering FE Civil All-in-One Exam Guide - Goswami, Indranil (McGraw-Hill's AccessEngineering., 2018)
This highly effective study guide offers 100% coverage of every subject on the FE Civil exam. This self-study resource contains all the information you need to prepare for and pass the challenging FE Civil exam. Written by a leading civil engineering educator and exam coach, Fundamentals of Engineering FE Civil All-in-One Exam Guide features clear explanations, exam strategies, and practice problems with fully worked solutions. Organized to exactly follow the order of the official exam syllabus, this effective study guide includes references to the official FE Reference Handbook along with tips on how to utilize that resource during the exam.